Influence of tropical leaf litter on nitrogen mineralization and community structure of ammonia-oxidizing bacteria - Diallo, MD.; Guisse, A.; Sall, SN.; Dick, RP.; Assigbetse, KB.; Dieng, AL.; Chotte, JL. (Biotechnologie, Agronomie, Société et Environnement, 2015)
Description of the subject. The present study concerns the relationships among leaf litter decomposition, substrate quality, ammonia-oxidizing bacteria (AOB) community composition and nitrogen (N) availability. Decomposition of organic matter affects the biogeochemical cycling of carbon (C) and N. Since the composition of the soil microbial community can alter the physiological capacity of the community, it is timely to study the litter quality effect on N dynamic in ecosystems. Objectives. The aim of this study was to determine the influence of leaf litter decomposition on N mineralization. The specific objectives of this study were to evaluate the influence of the litter biochemistry of five plants species (Faidherbia albida A.Chev., Azadirachta indica A.Juss., Casuarina equisetifolia L., Andropogon gayanus Kunth and Eragrostis tremula Hochst. ex Steud.) on N mineralization in a tropical ferrous soil (Lixisol), nitrification, and genetic diversity of ammonia-oxidizing bacteria. Denaturing gradient gel electrophoresis (DGGE) of amplified fragments of genes coding for 16S rRNA was used to study the development of bacterial communities during decomposition of leaf litter in soils. Method. Community structure of AOB was determined at two time periods: day 0 and day 140. Ten strains were tested and each of these strains produced a single band. Thus, DGGE DNA band patterns were used to estimate bacterial diversity. Plant secondary compounds such as polyphenols are purported to influence nutrient cycling by affecting organic matter degradation, mineralization rates, N availability and humus formation. In a laboratory study, we investigated the influence of six phenolic acids (ferulic, gallic, vanillic, syringic, p-coumaric and p-HBA acids) commonly found in the plant residues on N mineralization and NH4+ and NO3- production in soils. Results. The results showed that litter type did affect soil nitrification. Faidherbia albida litter was associated with increased inorganic N in soil after 140 days of incubation while A. gayanus and C. equisetifolia litter immobilized N. Azadirachta indica and E. tremula amendments had no significant effects in N mineralization. The results show that the addition of six phenolic acids significantly reduced NH4+ and NO3- compared to the control soil but had no significant effect on N mineralization. For the community of ammonium-oxidizing bacteria, a litter quality effect was noted, but the incubation time effect was more pronounced, except for C. equisetifolia litter. Conclusions. Results confirmed that the N mineralization changed with litter type under controlled conditions and the genetic structure of AOB is highly dependent on litter quality.